(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: It examines the Executives of Construction Party (Kargozaran-e Sazandegi) as one of the most prominent parties within Iran’s moderate reformist current. It explores the party’s origins and organizational development and analyzes its political and economic orientations and their impact on Iranian political life. Objective: The research aims to identify the party’s organizational structure and role in political participation, examine its views on governance, Wilayat al-Faqih (Guardianship of the Jurist), and foreign policy, and analyze its economic, cultural, and social orientations. Methodology: The research adopts a descriptive-analytical approach, relying primarily on Persian-language sources, particularly the party’s official website, its intellectual and media publications, and relevant academic literature. Results: The findings indicate that the party represents a major component of Iran’s moderate political current and has promoted policies centered on economic development, openness to the outside world, and strengthening the role of technocrats in state administration. However, its capacity to implement its political and economic programs remained constrained by the dominance of the conservative current in decision-making. Conclusion: The research concludes that the Executives of Construction Party has contributed to advancing reformist and developmental trends within Iran. Nevertheless, its political effectiveness has remained dependent on the prevailing balance of power within the Iranian political system.